Oral anticoagulant therapy in adults with congenital heart disease and atrial arrhythmias: Implementation of guidelines. (15th April 2018) - Yang, H.; Heidendael, J.F.; de Groot, J.R.; Konings, T.C.; Veen, G.; van Dijk, A.P.J.; Meijboom, F.J.; Sieswerda, G.Tj.; Post, M.C.; Winter, M.M.; Mulder, B.J.M.; Bouma, B.J.
Abstract: Background: Current guidelines on oral anticoagulation (OAC) in adults with congenital heart disease (ACHD) and atrial arrhythmias (AA) consist of heterogeneous and divergent recommendations with limited level of evidence, possibly leading to diverse OAC management and different outcomes. Therefore, we aimed to evaluate real-world implementation and outcome of three guidelines on OAC management in ACHD patients with AA. Methods: The ESC GUCH 2010, PACES/HRS 2014 and ESC atrial fibrillation (AF) 2016 guidelines were assessed for implementation. ACHD patients with recurrent or sustained non-valvular AA from 5 tertiary centers were identified using a national ACHD registry. After two years of prospective follow-up, thromboembolism, major bleeding and death were assessed. Results: In total, 225 adults (mean age 54 ± 15 years, 55% male) with various defects (simple 43%; moderate 37%; complex 20%) and AA were included. Following the most strict indication (OAC is recommended in all three guidelines), one should treat a mere 37% of ACHD patients with AA, whereas following the least strict indication (OAC is recommended in any one of the three guidelines), one should treat 98% of patients. The various guidelines were implemented in 54–80% of patients. From all recommendations, Fontan circulation, CHA2DS2-VASc ≥ 1 and AF were independently associated with OAC prescription. Superiority of any guideline in identifying outcome (n = 15) could not be demonstrated. Conclusions: The implementation of current guidelines on OAC management in ACHD patients with AA is low, probably due to substantial heterogeneity among guidelines. OAC prescription in daily practice was most consistent in patients with AF and CHA2DS2-VASc ≥ 1 or Fontan circulation. Highlights: Current guidelines on oral anticoagulation for AA in ACHD are heterogeneous. Implementation of current guidelines on oral anticoagulation for AA in ACHD is low. Implementation was the highest in patients with CHA2DS2-VASc ≥ 1 or Fontan circulation. Efforts are needed to unify and strengthen guidelines on oral anticoagulants in ACHD.